IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS DI TAMAN PENDIDIKAN QUR’AN AL-AZIZ JABUNG MALANG - Zulfa Mufarokhah; Maskuri Maskuri; Mutiara Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The purpose of this study is to describe the values of religious character education, planning for inculcation of religious character education, implementation of religious character education, and models for implementing religious character education. This study uses a qualitative research approach and uses case study research and data collection using observation, interviews and documentation, the population of this study is the students of TPQ Al-Aziz Jabung. Based on the research results obtained by the research findings are: 1). The values of religious character education instilled in TPQ are implemented by imitating the example of the prophet namely shidiq, amanah, tabligt and fathonah. 2). planning the planting of religious character education values in the TPQ includes preparing learning materials on the TPQ by using the book of taufik's embroidery book, the book of Sholawat, the Qur'an. In using learning, Ustadzah also prepared carefully, among others, the analysis of the media / visual aids used. With planning it is expected that everything that has been programmed within a certain time can be achieved to the maximum. 3). the implementation of planning to plant the values of religious character in the TPQ that is carrying out the implementation process in the classroom by reading the prayer before starting the lesson, with the aim that students to pray first before carrying out activities, then reading the book, and reading the Qur'an so that the length can be short in read it. Other activities such as the reading of the Rotibul Hadad, the reading of Sholawat of the Prophet SAW. 4). the model of implementation of religious character education in TPQ is implementation in the classroom, both in terms of approaches, strategies and methods. Which is adjusted to the needs of students.